THE BEHAVIOR IN USING OF PESTICIDES ON RICE FARMERS AT RJ VILLAGE BANDAR LAMPUNG - Fitria Saftarina (JUKE Unila, 2014)
Background: Based on the Health Law No. 36 year 2009 part 164(1) and (2) about the Occupational Health mandates that every workplace should hold an Occupational Health and Safety (OHS) to prevent health problems for workers. This is also include for workers in the agricultural sector that uses pesticides. The behavior of using pesticide must be on the rules set by the Ministry of Health of the Republic of Indonesia. Study about the behavior of using pesticides on farmers at the RJ village of Bandar Lampung. Method: Design of this study was a cross sectional study. Sample of this study 50 farmers. Data were collected by using interviews and questionnaire. The behavior of using pesticides include: the use of Personal Protective Equipment (PPE), the direction of spraying, washing hands after spraying, changing clothes after spraying, taking a bath after spraying, and smoking after spraying. Result: The use of PPE was complete about 8%, spraying pesticide in the direction of the wind about 80%, washing hands after spraying about 66%, changing clothes after spraying about 82%, taking a bath after spraying about 66% and smoking after spraying about 50%. Conclusion: Behavior on using PPE and smoking after spraying was low. All sectors need to support farmers’ behavior to use pesticides wisely. The impact is to increase farmers’ health status. [JuKe Unila 2014; 4(8):180-184]